Subjective and objective evaluation of masticatory function in patients with bimaxillary implant‐supported prostheses. (1st December 2022) - Homsi, George; Karlsson, Anna; Almotairy, Nabeel; Trulsson, Mats; Kumar, Abhishek; Grigoriadis, Anastasios
Abstract: Background: People perform poorly in masticatory function tests despite well‐functioning prostheses. However, it is unclear whether there is an agreement between subjective and objective measures of mastication. Objectives: To investigate the association between subjective and objective measures of masticatory function in patients with bimaxillary implant‐supported prostheses. Materials and Methods: An experimental group ( n = 25, age = 70.6 ± 7.5 years, eight women) with bimaxillary implant‐supported fixed prostheses and a control group ( n = 25, age = 69.0 ± 5.3, 13 women) with natural dentition were recruited. The participants in the experimental group were included if they had been using the prosthesis for at least a year and had no obvious complaints with their prostheses. The control group was people with natural dentition and without any prostheses or complaints related to the masticatory system. The masticatory function was evaluated objectively with food comminution and mixing ability tests, and subjectively with jaw function limitation scale (JLFS) and oral health impact profile (OHIP). Results: The experimental group performed poorly in both objective tests (p < .001). However, there was no significant differences between the two groups in total JFLS ( p = .114) and OHIP ( p = .312) scores. Though, there were certain positive correlations between the food comminution test and JFLS subdomains in the control group, and a positive correlation between food comminution test and specific subdomains of OHIP in the experimental group indicating poor correlation between the subjective and objective measures. Conclusion: Although patients with implant prostheses show poor masticatory performance, there is no agreement in the objective and subjective measures of mastication. Abstract : Masticatory function in people treated with bimaxillary implant‐supported fixed prostheses in comparison to people with natural dentitions.